Optimizing Youtube as a Digital Platform to Enhance Listening Skills Among Eleventh-Grade Students at MAN 1 Simeulue, Indonesia - Ridwan Ridwan; Ridwan Riskayanti (Journal Of Social Siences And Islamic Studies (JOSIS), 2026)
This research explores the capabilities of YouTube as a digital medium to boost listening comprehension among eleventh-grade learners at MAN 1 Simeulue, a rural Islamic senior high institution in Aceh, Indonesia. Listening is commonly regarded as one of the most difficult competencies in English as a Foreign Language (EFL) instruction, especially in rural settings where authentic exposure and digital resources are scarce. To fill this void, the study utilized a quasi-experimental approach involving 60 students, split evenly into an experimental cohort and a control cohort. The experimental cohort was subjected to YouTube-integrated teaching, while the control cohort engaged in traditional textbook-based listening activities. Data were gathered through pre-tests, post-tests, in-class observations, and instructor notes, then analyzed using paired and independent sample t-tests. The outcomes indicated that both cohorts improved in listening comprehension; nonetheless, the experimental cohort demonstrated significantly greater progress in performance, motivation, and classroom interaction. These findings underscore YouTube’s versatility as an accessible, budget-friendly resource for language teaching. The study contributes empirical insights from a rural Islamic educational context and provides practical recommendations for teachers, curriculum designers, and policymakers aiming to bridge educational gaps through digital learning